Diseño y construcción de una máquina para la rehabilitación de personas con movilidad reducida en sus extremidades inferiores - Solórzano Palacios, Yelibert Giovanny (2023)
This study describes the complete design and construction process of a walker-type rehabilitation machine that will aid in the recovery of patients with mobility limitations, specifically those who suffer from functional or articular deficiencies in the lower extremities, and who require active assistance. The project is led by students from the Facultad de Ciencias de la Ingeniería de la Universidad Técnica Estatal de Quevedo. This process consists of several implementation phases. The first phase involves selection and design using SolidWorks CAD software. This software is used to identify the critical points considering the displacement of the structure, in this case, which was less than 1 mm. In addition, it was ensured that it did not exceed the elastic limit and that its safety factor is greater than unity, all based on the material selection. In the second phase, an analysis was performed to ensure the reliability of the design, considering the results obtained. Subsequently, plans were generated to carry out the third phase, which is to manufacture the machine. In this stage, load tests similar to those of the analysis were carried out in the software, with the objective of guaranteeing the functionality of the machine